Anti‐CD22 and anti‐CD79b antibody‐drug conjugates preferentially target proliferating B cells. (6th March 2017) - Fuh, Franklin K; Looney, Caroline; Li, Dongwei; Poon, Kirsten A; Dere, Randall C; Danilenko, Dimitry M; McBride, Jacqueline; Reed, Chae; Chung, Shan; Zheng, Bing; Mathews, William Rodney; Polson, Andrew; et al.
Abstract : Background and Purpose: CD22 and CD79b are cell‐surface receptors expressed on B‐cell‐derived malignancies such as non‐Hodgkin's lymphoma (NHL). An anti‐mitotic agent, monomethyl auristatin E, was conjugated to anti‐CD22 and anti‐CD79b antibodies to develop target‐specific therapies for NHL. The mechanism of action (MOA) and pharmacological and pharmacokinetic (PK) profiles of these antibody‐drug conjugates (ADCs) were investigated in cynomolgus monkeys. Experimental Approach: Animals were administered anti‐CD22 or anti‐CD79b ADCs, respective unconjugated antibodies or vehicle. Pharmacodynamic effects on total and proliferating B cells and serum PK were then assessed. Antibody‐dependent cellular cytotoxicity (ADCC) and complement‐dependent cytotoxicity (CDC) of the ADCs were evaluated in vitro . Key Results: Depletion of B cells was observed after administration of either ADC or the respective unconjugated antibodies. An extended duration of depletion was observed in animals administered ADCs. Similarly, preferential depletion of proliferating B cells in blood and germinal centre B cells in spleen were only observed in animals administered ADCs. Serum PK profiles of ADCs and respective unconjugated antibodies were comparable. In vitro, anti‐human CD22 and anti‐human CD79b antibodies showed no or only moderate ADCC activity, respectively; neither antibody had CDC activity. Conclusions and Implications: The findings support the proposed MOA: initial depletion of total B cells by antibody‐mediated opsonization, followed by preferential, sustained depletion of proliferating B cells by the auristatin conjugate due to its anti‐mitotic action. Delivering potent anti‐mitotic agents to B cells via the specificity of monoclonal antibodies provides a means to eliminate pathogenic B cells in NHL with improved risk–benefit profiles over traditional chemotherapeutics.